2002
DOI: 10.4049/jimmunol.168.1.224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Isotype of the Light Chain on the Properties of IgG

Abstract: It is widely appreciated that the isotype of the H chain of the Ab molecule influences its functional properties. We have now investigated the contribution of the isotype of the L chain to the structural and functional properties of the Ab molecule. In these studies, the L chain variable region of a murine anti-dansyl Ab was joined to either human κ or λ constant region domains and expressed with mouse-human chimeric H chains of the four human IgG isotypes. The resulting Abs were secreted as fully assembled mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 39 publications
3
45
1
Order By: Relevance
“…Although deposited 1HZH coordinates were numbered in Kabat and Wu format, the residue numbering in this figure is in Eu format, the same as in Table 1 equal amounts for IgG2 and IgG2. Previous reports (4,32,33) have shown that the LC type can impact antigen/receptor binding and in vivo clearance. Some of these results were linked to specific differences in flexibility between the -and -LC, and, as we have shown in this report, may also be attributed to different distribution of IgG2 isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Although deposited 1HZH coordinates were numbered in Kabat and Wu format, the residue numbering in this figure is in Eu format, the same as in Table 1 equal amounts for IgG2 and IgG2. Previous reports (4,32,33) have shown that the LC type can impact antigen/receptor binding and in vivo clearance. Some of these results were linked to specific differences in flexibility between the -and -LC, and, as we have shown in this report, may also be attributed to different distribution of IgG2 isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another well-established functional difference between and antibodies is the interaction of chains with the bacterial surface protein L (20,24). It has also been demonstrated that the isotype of the IGL chain can influence the kinetics of the intracellular assembly of antibodies and the susceptibility of the interchain disulfide bonds to reducing agents (25). A different kind of functional differentiation between and antibodies was indicated by Wardemann et al (2004) (26).…”
Section: Genementioning
confidence: 99%
“…However, although class IgG antibodies are quite a homogeneous population, there are structural differences among the subclasses in one species (Montano and Morrison 2002) and among antibodies derived from different hosts. Interestingly, the biggest structural variations have been observed in the hinge region and the Fc fragment (Kabat 1967).…”
Section: Introductionmentioning
confidence: 99%